Ecophysiological characteristics of wintering mute swan population in anthropogenically modified environments. Issue 1 (31st December 2022) - Tkachenko, H.; Hetmański, T.; Włodarkiewicz, A.; Jarosiewicz, A.; Tomin, V.; Kamiński, P.; Kurhaluk, N.
Abstract: Environmental responsibility is becoming part of the social profile of modern society on an international scale. The analysis of ecosystems in the Baltic Sea presents an example of the use and functioning of ecological systems under increased anthropogenic pressure globally. Wintering and feeding swans, i.e. birds wintering in large urban agglomerations, are particularly useful bioindicators of the degrees of environmental pollution. The aim of the study was to assess the element concentrations in the soil of the birds' habitat and compare these results with metal contents in birds' feathers and oxidative stress data [diene conjugates (DC) and middle-mass molecules (MM), the activity of superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), and glutathione peroxidase (GPx), and the total antioxidant status (TAS)] in a wintering population of the mute swan ( Cygnus olor ) living in northern Poland (southern Baltic Sea). Soil samples collected from bird habitats in Słupsk, Gdynia, and Sopot. These areas differ in the levels of anthropogenic pressure (urban agglomerations, recreational activity, and tourism). The analysis showed significant differences in the Al, Si, Ti, Mn, Fe, Cu, Zn, Zr, Rh, and Ru levels between the soil from Słupsk and both Gdynia and Sopot areas and in the Rh and Ru content between all studied areas. Our results indicated high dependence on the localization, age, and sex of the birds, which were assessed by the level of DC in the blood. The study showed a connection between the lipid peroxidation and antioxidant system functioning, high MM values, and a decreased level of the TAS in adult males from Słupsk, compared to juvenile males from the same area. The functioning of the antioxidant system reflected in the activity of antioxidative enzymes and TAS values was as follows: GR > SOD > CAT > GPx and TAS.